Adoptive immune cell therapy for colorectal cancer - Liu, Chenxiao; Liu, Nan; Zhang, Tongcun; Tu, Yanyang (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is a major cause of cancer-related morbidity and mortality worldwide, with limited options for patients at advanced stages. Immunotherapy, particularly immune cell-based therapies, has gained significant attention as an innovative approach for targeting CRC. This review summarizes the progress in various immune cell therapies, including DC vaccine, CAR/TCR-T cells, CAR-NK cells et al, each engineered to recognize and attack cancer cells expressing specific antigens. CAR-T cell therapy, which has been successful in hematologic cancers, faces challenges in CRC due to the solid tumor microenvironment, which limits cell infiltration and persistence. CAR-NK cells, CAR-M and CAR-γδ T cells, however, offer alternative strategies due to their unique properties, such as the ability to target tumor cells without prior sensitization and a lower risk of inducing severe cytokine release syndrome. Recent advances in lentiviral transduction have enabled effective expression of CARs on NK and γδ T cells, providing promising preclinical results in CRC models. This review explores the mechanisms, tumor targets, preclinical studies, and early-phase clinical trials of these therapies, addressing key challenges such as enhancing specificity to tumor antigens and overcoming the immunosuppressive tumor microenvironment. The potential of combination therapies, including immune checkpoint inhibitors and cytokine therapy, is also discussed some as a means to improve the effectiveness of immune cell-based treatments for CRC. Continued research is essential to translate these promising approaches into clinical settings, offering new hope for CRC patients.